A Review of Social Media Advertising and the Impact of Digital Marketing on MSME Growth: SLR - Wahyudi, Eko Juni; Astuti, Hastirin Widi; Wahid, Moehammad Nasri Abdoel; Djoewita, Djoewita; Yustika, Siska (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
The main objective of this study is to analyze existing literature on the impact of digital marketing on Micro, Small, and Medium Enterprises (MSMEs). Novelty: The findings show that digital marketing began to be noticed by large companies during the emergence of Web 2.0. Research Method: The method used a systematic literature review approach using the Scopus database with the keywords digital marketing and MSMEs. This study provides insight into the development of digital marketing and the impact of digital marketing on MSMEs. The practical implications of this research are that this study provides a theoretical analysis of the benefits received by MSMEs if they adopt digital marketing and that this study also provides further scope for digital marketers to approach their targets. The results of this study can be a valuable guide for companies in optimizing their marketing strategies in this digital era. Conclusion: This study is highly relevant considering the important role of social media in driving current marketing strategies. By examining social media advertising reviews and their impact on growth, this study can provide a deeper understanding of the effectiveness of digital marketing campaigns. Through careful analysis, this study can identify the factors that influence the success of social media advertising and how it impacts business growth.